Intra- and early postoperative complications after standard cataract surgery or femtosecond laser-assisted cataract surgery combined with pars plana vitrectomy in cases of retinal diseases. Issue 1 (2021) - Hengerer, Fritz H.; Auffarth, Gerd U; Conrad-Hengerer, Ina
No abstract available